Coevolution of generalist feeding ecologies and gyrencephalic mushroom bodies in insects - Farris, Sarah M. (National Academy of Sciences, 2005)
Here we demonstrate the independent acquisition of strikingly similar brain architectures across divergent insect taxa and even across phyla under similar adaptive pressures. Convoluted cortical gyri-like structures characterize the mushroom body calyces in the brains of certain species of insects; we have investigated in detail the cellular and ecological correlates of this morphology in the Scarabaeidae (scarab beetles). “Gyrencephalic” mushroom bodies with increased surface area and volume of calycal synaptic neuropils and increased intrinsic neuron number characterize only those species belonging to generalist plant-feeding subfamilies, whereas significantly smaller “lissencephalic” mushroom bodies are found in more specialist dung-feeding scarab beetles. Such changes are not unique to scarabs or herbivores, because the mushroom bodies of predatory beetles display similar morphological disparities in generalists vs. specialists. We also show that gyrencephalic mushroom bodies in generalist scarabs are not associated with an increase in the size of their primary input neuropil, the antennal lobe, or in the number of antennal lobe glomeruli but rather with an apparent increase in the density of calycal microglomeruli and the acquisition of calycal subpartitions. These differences suggest changes in calyx circuitry facilitating the increased demands on processing capability and flexibility imposed by the evolution of a generalist feeding ecology.